2013
DOI: 10.1214/12-aos1014
|View full text |Cite
|
Sign up to set email alerts
|

Minimax bounds for sparse PCA with noisy high-dimensional data

Abstract: We study the problem of estimating the leading eigenvectors of a high-dimensional population covariance matrix based on independent Gaussian observations. We establish a lower bound on the minimax risk of estimators under the l2 loss, in the joint limit as dimension and sample size increase to infinity, under various models of sparsity for the population eigenvectors. The lower bound on the risk points to the existence of different regimes of sparsity of the eigenvectors. We also propose a new method for estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
137
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 33 publications
2
137
1
Order By: Relevance
“…Recent research (e.g. [18,19]) has examined how well underlying 'population' PCs are estimated by the sample PCs in the case where n p, and it is shown that in some circumstances there is little resemblance between sample and population PCs. However, the results are typically based on a model for the data which has a very small number of structured PCs, and very many noise dimensions, and which has some links with recent work in RPCA (see §3c).…”
Section: (Iii) Centringsmentioning
confidence: 99%
“…Recent research (e.g. [18,19]) has examined how well underlying 'population' PCs are estimated by the sample PCs in the case where n p, and it is shown that in some circumstances there is little resemblance between sample and population PCs. However, the results are typically based on a model for the data which has a very small number of structured PCs, and very many noise dimensions, and which has some links with recent work in RPCA (see §3c).…”
Section: (Iii) Centringsmentioning
confidence: 99%
“…Third, the most relevant result to statisticians is the Tracy-Widom law (Tracy and Widom, 1996) studied by Widom (1996, 2000), Johnstone (2001Johnstone ( , 2008, Birnbaum et al (2013), and many others. The main result is as follows; Suppose that X = (X ij ) p×n has entries which are iid N (0, 1).…”
Section: Results On Graph Theorymentioning
confidence: 99%
“…Recently, Pillai and Yin (2012) showed that the largest eigenvalue of the correlation matrix also follows the same distribution. Recently, Birnbaum et al (2013) studied minimax bounds in the sparse spiked distribution, where the covariance matrix Σ is not an identity matrix but…”
Section: Results On Graph Theorymentioning
confidence: 99%
See 2 more Smart Citations